(untitled) (Revista Brasileira de Contabilidade e Gestão, 2012)
The study aims to verify whether the plans of teaching-learning of undergraduate degree in accounting from a University in the South of the country include the basic elements necessary for its preparation. The research characterized as descriptive, documentary and quantitative approach. Were analyzed the teaching-learning of plans 35 disciplines that constitute the curriculum of this course, belonging to a University in southern Brazil. Data collection was performed by the query on the electronic site of the institution. We analyzed each plan of teaching-learning process and whether this presents the basic elements in all parts of its structure, each part was observed in the light of the topics described by Silveira (2005) by means of a checklist. The results show that five disciplines had 80% compatibility of teaching-learning plans. As worst scores three disciplines that had less basic elements, with degree of compatibility of 40%. the questions that comprise the checklist, two questions have achieved better performance, which represents an average of 94.29% positive answers. One question stands out, with an average of 28.57 %, with being presented the worst performance in the analysis of the checklist. We conclude, that on average 63 % of the plans of the teaching-learning undergraduate degree in Accounting include the basic elements necessary to constitute the plan of teaching and learning.